Implementasi Dan Tantangan Perlindungan Hukum Terhadap Hak-Hak Pekerja Dalam Hubungan Kerja Di Indonesia - Jihan Rafifah; Riyanti Angelina; Enjum Jumhana; Nazwa Aura Fatima; Wafiroh (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research examines legal protection of workers' rights in Indonesia. This study uses a qualitative and normative approach, analyzing applicable labor law. Even though Indonesia has a comprehensive legal framework, there is still a gap between regulation and implementation. This research identifies three main aspects of legal protection: economic, social, and technical. This study also found barriers to implementation, including regulatory factors, culture and company capabilities. This research recommends the government's active role in improving regulations, supervision and law enforcement, as well as building awareness of all parties regarding the responsibilities and roles of individuals in building harmonious and just industrial relations